2012
DOI: 10.1111/j.1939-165x.2012.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of theRivalta test for feline infectious peritonitis

Abstract: Sensitivity, specificity, and PPV of the Rivalta test for the diagnosis of FIP were lower than previously reported except when used in young cats. The components in effusions that lead to a positive Rivalta test remain unknown, but the positivity is not simply related to high total protein concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
1
47
0
1
Order By: Relevance
“…A positive Rivalta test was once believed to be highly specific for FIP fluid. In a study of 497 cats with effusions, 35% of which had confirmed FIP, the Rivalta test had a sensitivity of 91% and a specificity of 66%, with a positive predictive value of 58% and a negative predictive value of 93% (Fischer et al, 2012). As would be expected, these values increased when cats with lymphosarcoma or bacterial infections were excluded, or when only cats of ≥2 years of age were considered.…”
Section: Rivalta Testmentioning
confidence: 81%
“…A positive Rivalta test was once believed to be highly specific for FIP fluid. In a study of 497 cats with effusions, 35% of which had confirmed FIP, the Rivalta test had a sensitivity of 91% and a specificity of 66%, with a positive predictive value of 58% and a negative predictive value of 93% (Fischer et al, 2012). As would be expected, these values increased when cats with lymphosarcoma or bacterial infections were excluded, or when only cats of ≥2 years of age were considered.…”
Section: Rivalta Testmentioning
confidence: 81%
“…Slowly layer one drop of the effusion fluid to the surface of the acetic acid solution. The sensitivity and specificity of the Rivalta test are reported to be 91.3% and 65.5%, respectively (Fischer et al, 2012). 6-14C).…”
Section: Feline Infectious Peritonitismentioning
confidence: 97%
“…To perform this relatively simple test, place one drop of 98% acetic acid into 5-mL distilled water and mix well in a clear reagent tube. This test has a recently reported PPV of 58.4% to 88.4% and NPV of 66.7% to 93.4% (Fischer et al, 2012) in contrast to PPV of 86% and NPV of 97% in an earlier study (Hartmann et al, 2003). A positive test requires that the drop of effusion retain its form on the surface or slowly sink to the bottom as a droplet or jellyfish-like shape ( Fig.…”
Section: Feline Infectious Peritonitismentioning
confidence: 98%
See 1 more Smart Citation
“…1,2 Traditionally, the specimens of ascites are classified into broad categories of transudates or exudates according to AFTP concentration. 6,7 Samples are categorized as transudates, if the AFTP is less than 25 g/L and as exudates if AFTP is greater than 25 g/L. Exudative ascites caused by an inflammatory or malignant tumor is high in protein; transudative ascites caused by cirrhosis, heart failure, and nephrotic syndrome is low in protein due to an imbalance of Starling forces.…”
Section: Introductionmentioning
confidence: 99%